2009
DOI: 10.1002/anie.200803447
|View full text |Cite
|
Sign up to set email alerts
|

Core–Shell PbI2@WS2 Inorganic Nanotubes from Capillary Wetting

Abstract: Multiwall WS2 nanotube templates were used as hosts to prepare core–shell PbI2@WS2 nanotubes by a capillary‐wetting method. Conformal growth of PbI2 layers on the inner wall of the relatively wide WS2 nanotubes (i.d. ca. 10 nm) leads to nanotubular structures which were not previously observed in narrow carbon nanotube templates. Image simulation after structural modeling (see picture) showed good agreement with the experimental HRTEM image.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
49
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 29 publications
3
49
0
Order By: Relevance
“…Various forms of PbI 2 including thin films, nano-clusters, multiwalled nanotubes of lead iodide have been experimentally explored [34][35][36][37][38] . The successful growth of single-layered PbI 2 nanotubes within the carbon nanotubes was reported in most recent experiment 39 .…”
Section: Introductionmentioning
confidence: 99%
“…Various forms of PbI 2 including thin films, nano-clusters, multiwalled nanotubes of lead iodide have been experimentally explored [34][35][36][37][38] . The successful growth of single-layered PbI 2 nanotubes within the carbon nanotubes was reported in most recent experiment 39 .…”
Section: Introductionmentioning
confidence: 99%
“…Capillary filling has been extended for the case of inorganic nanotubes, including sulfides WS 2 and MoS 2 . The filling of sulfide nanotubes can differ from that of CNTs ,. Due to the higher strain energies of inorganic nanotubes, their diameters are an order of magnitude larger than those of CNTs, which may facilitate the formation of not only nanowires, but also nanotubes of the encapsulated compound, by wetting the inner surface.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the higher strain energies of inorganic nanotubes, their diameters are an order of magnitude larger than those of CNTs, which may facilitate the formation of not only nanowires, but also nanotubes of the encapsulated compound, by wetting the inner surface. Experimental studies on the cooling of PbI 2 BiI 3 , and SbI 3 melts within WS 2 nanotubes indicated the formation of core‐shell heterostructures – nanotubes of layered iodides inside sulfide nanotubes (PbI 2 @WS 2 , BiI 3 @WS 2 , and SbI 3 @WS 2 ) ,. The encapsulation of non‐layered salts like CsI into WS 2 nanotubes reveals the formation of nanowires only .…”
Section: Introductionmentioning
confidence: 99%
“…Early efforts have focused on using a tubular template to confine the formation of nanowires or nanotubes. For example, PbI 2 nanotubes have been synthesized within the inner cavities of WS 2 nanotubes or carbon nanotubes (CNTs) by capillary wetting . In order to facilitate precursor penetration, the nanotube ends must be opened and a long‐term thermal annealing process (up to 1 month) is usually carried out .…”
mentioning
confidence: 99%
“…For example, PbI 2 nanotubes have been synthesized within the inner cavities of WS 2 nanotubes or carbon nanotubes (CNTs) by capillary wetting . In order to facilitate precursor penetration, the nanotube ends must be opened and a long‐term thermal annealing process (up to 1 month) is usually carried out . As the growth process is confined within a nanotube template, the diameter of the target nanotubes, their structural continuity, and their uniformity will be influenced by the channel size of the template.…”
mentioning
confidence: 99%